(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article provides facilities for teachers in distance training. Information on the forms of distance training (lecture, consultation, laboratory, practical, control work, independent work, webinar) and teaching methods (reproductive, problem-based learning, heuristic, scientific research, design, game) is provided.